2008
DOI: 10.1007/s00441-008-0658-9
|View full text |Cite
|
Sign up to set email alerts
|

Brain endothelial cells and the glio-vascular complex

Abstract: We present and discuss the role of endothelial and astroglial cells in managing the blood-brain barrier (BBB) and aspects of pathological alterations in the BBB. The impact of astrocytes, pericytes, and perivascular cells on the induction and maintenance of the gliovascular unit is largely unidentified so far. An understanding of the signaling pathways that lie between these cell types and the endothelium and that possibly are mediated by components of the basal lamina is just beginning to emerge. The metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
262
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(268 citation statements)
references
References 248 publications
2
262
0
Order By: Relevance
“…Evidence to support the involvement of the cytoskeleton derives from observations of barrier permeability and actin integrity. Signaling from b 1 -integrin involves activation of the actin cytoskeleton (Wolburg et al, 2009). In addition, TJ proteins including ZO-1, occludin, and claudin-5 bind to the cytoskeleton actin.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence to support the involvement of the cytoskeleton derives from observations of barrier permeability and actin integrity. Signaling from b 1 -integrin involves activation of the actin cytoskeleton (Wolburg et al, 2009). In addition, TJ proteins including ZO-1, occludin, and claudin-5 bind to the cytoskeleton actin.…”
Section: Discussionmentioning
confidence: 99%
“…In their study of traumatic brain injury induced by controlled cortical impact, Myer et al (2006) concluded that reactive astrocytes play essential protective roles, by preserving neural tissue and restricting inflammation after moderate brain injury. In the present study, a single HIFU exposure was sufficient to elicit an elevation in GFAP immunostaining in astrocytes, a characteristic neuro-immune response to blood-brain barrier cellular injury or infection (Abbott et al 2010;Chodobski et al 2011;Wolburg et al 2009). In this study, the animals were followed for only 24 h; a longer survival time is needed to establish the profile of astroglial activation.…”
Section: Discussionmentioning
confidence: 51%
“…At the inner BRB, the retinal endothelial cells form a tightly sealed monolayer, separating the abluminal (retina side) and luminal (blood side) domains of the retinal endothelium, and prevent paracellular transport of materials across endothelial cells between the retina and circulating blood (Wolburg et al, 2009). In particular, D-mannitol, a representative nonpermeable paracellular marker, exhibits very low blood-to-retina influx permeability while D-glucose and amino acids, the substrates of membrane transporter molecules, exhibit over a 300-fold higher permeability than that of D-mannitol (Puchowicz et al, 2004;).…”
Section: Molecular Aspects Of the Barrier Structurementioning
confidence: 99%